Nonalcoholic steatofibrosis independently predicts mortality in nonalcoholic fatty liver disease. Issue 5 (6th June 2017) - Younossi, Zobair M.; Stepanova, Maria; Rafiq, Nila; Henry, Linda; Loomba, Rohit; Makhlouf, Hala; Goodman, Zachary
Abstract : Nonalcoholic steatohepatitis (NASH) is the progressive form of nonalcoholic fatty liver disease (NAFLD). The minimal pathologic criteria for NASH include hepatic steatosis, ballooning degeneration, and lobular inflammation. The resolution of NASH, which relies on the loss of ballooning degeneration, is subject to sampling and observer variability in pathologic interpretation. Ballooning is associated with advanced hepatic fibrosis in cross‐sectional studies but is not a predictor of mortality in NAFLD. Fibrosis staging, while still subject to some sampling variability, has less observer variability and is a robust predictor of liver‐related mortality in NAFLD. In this study, we hypothesize that, regardless of the diagnosis of NASH, the presence of steatofibrosis (steatosis accompanied by fibrosis) regardless of other pathologic features can also be a robust predictor of mortality in NAFLD. We used our previously reported cohort of patients with NAFLD with liver biopsies and long‐term mortality follow‐up. Cox proportional hazard models were used to determine the predictors of overall and liver‐related mortality. Of 209 enrolled NAFLD subjects, 97 can be classified as having steatofibrosis. During follow‐up (median 150 months), 64 (30.6%) patients died, with 18 (8.6%) from liver‐related causes. Adjusted for age, both diagnostic categories of NASH and steatofibrosis were significantly and similarly associated with liver‐related mortality (adjusted hazard ratio [aHR], 9.9; 95% confidence interval (CI), 1.3‐74.9; P = 0.027; aHR, 6.7; 95% CI, 1.5‐29.8; P = 0.013, respectively). However, only steatofibrosis showed independent association with overall mortality (aHR, 1.76; 95% CI, 1.02‐3.05; P = 0.043). Conclusion : Steatofibrosis and NASH are similarly associated with liver‐related mortality, but only steatofibrosis is associated with overall mortality in patients with NAFLD. Given the inherent observer variability in ballooning degeneration, a key diagnostic component of NASH, we suggest that steatofibrosis should be considered a viable diagnostic classification for NAFLD subjects at risk or adverse outcomes and provides a simpler endpoint for clinical trials of therapeutic agents. ( Hepatology Communications 2017;1:421–428)